A comprehensive review on the potential of coumarin and related derivatives as multi-target therapeutic agents in the management of gynecological cancers - Şeker Karatoprak, Gökçe; Dumlupınar, Berrak; Celep, Engin; Kurt Celep, Inci; Küpeli Akkol, Esra; Sobarzo-Sánchez, Eduardo (Frontiers in Pharmacology, 2024)
Current treatments for gynecological cancers include surgery, radiotherapy, and chemotherapy. However, these treatments often have significant side effects. Phytochemicals, natural compounds derived from plants, offer promising anti-cancer properties. Coumarins, a class of benzopyrone compounds found in various plants like tonka beans, exhibit notable antitumor effects. These compounds induce cell apoptosis, target PI3K/Akt/mTOR signaling pathways, inhibit carbonic anhydrase, and disrupt microtubules. Additionally, they inhibit tumor multidrug resistance and angiogenesis and regulate reactive oxygen species. Specific coumarin derivatives, such as auraptene, praeruptorin, osthole, and scopoletin, show anti-invasive, antimigratory, and antiproliferative activities by arresting the cell cycle and inducing apoptosis.They also inhibit metalloproteinase-2 and -9, reducing tumor cell migration, invasion, and metastasis. These compounds can sensitize tumor cells to radiotherapy and chemotherapy.Synthetic coumarin derivatives also demonstrate potent antitumor and anticancer activities with minimal side effects. Given their diverse mechanisms of action and minimal side effects, coumarin-class phytochemicals hold high potential as therapeutic agents in gynecological cancers, potentially improving treatment outcomes and reducing side effects. This review will aid in the synthesis and development of novel coumarin-based drugs for these cancers.